Physical and chemical changes in guava (Psidium guajava, L) on maturity - Salmah Yusof (Universiti Pertanian Malaysia, 2016)
The physical and chemical changes occuring during development and maturity of guava (Vietnamese variety) were studied. The weight increase, reduction in hardness, total pectin content, and changes in ascorbic acid level showed a sigmoid curve. The weight increase sa maximum between the 10th-12th week. Reduction in hardness, changes in pectin and ascorbic acid content occured most between the 12th and 14th week. Reduction in chlorophyll content, increase in fruit diameter, sugar content and water soluble pectin fraction showed a more linear change. Fructose level was highest among the three sugars maturity. The density of the fruit increased rapidly at the beginning, remained constant between the 4th to 12th week and then decreased again. The moisture content increased rapidly at first, followed by a more gradual increase and remained constant after the 14th week. The pH of the Vietnamese guava fluctuated, being fairly acidic at 4 weeks (pH 4.5), least acidic at the 10th week (pH 5.4) and was acidic again on maturity (pH 4.05). The tannin level was high in immature guava but dropped drastically after the 8th week, and remained at a constant low level after the 10th week. Soluble pectin increased during development and maturity. Insoluble pectin were partly converted to soluble pectin during maturity (after 14 weeks).